2005
DOI: 10.1111/j.1365-2036.2005.02542.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine therapy in chronic delta hepatitis: a multicentre randomized‐controlled pilot study

Abstract: SUMMARYBackground: Delta virus (HDV)-related chronic hepatitis is difficult to treat. Aims: To evaluate the efficacy of lamivudine 100 mg daily on serum HDV-RNA, hepatitis D virus antibodies and alanine aminotransferase levels, liver histology, and on hepatitis B surface antigen seroconversion. Methods: Thirty-one hepatitis B surface antigen-positive, HDV-RNA-positive patients with ALT ‡ 1.5 upper normal level and compensated liver disease were randomized (1:2 ratio) to placebo (group A, n ¼ 11) or lamivudine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 22 publications
(22 reference statements)
2
66
1
8
Order By: Relevance
“…One would expect that administering lamivudine to individuals with chronic HBV and HDV would also reduce HDV levels. However, studies have shown that administering lamivudine has no significant effect on the levels of HDV RNA in infected patients [9,11,23,10]. Even after months of treatment, HDV viral production and liver damage (i.e.…”
Section: Lamivudine Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…One would expect that administering lamivudine to individuals with chronic HBV and HDV would also reduce HDV levels. However, studies have shown that administering lamivudine has no significant effect on the levels of HDV RNA in infected patients [9,11,23,10]. Even after months of treatment, HDV viral production and liver damage (i.e.…”
Section: Lamivudine Treatmentmentioning
confidence: 99%
“…infection) remain high. Furthermore, HBV levels can return post treatment [9,11]. It is believed that lamivudine inhibits HBV replication downstream of RNA production, which allows for continued production of HBsAg [9].…”
Section: Lamivudine Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination treatments performed so far have not been shown as more effective than interferon treatment alone (39,(41)(42)(43)(44)46). However, with new treatments currently under investigation in phase 2 studies combination treatment may become a viable option (47).…”
Section: Response To Antiviral Treatmentmentioning
confidence: 99%
“…Thus, an effective anti-HDV therapy would require a marked suppression of HBsAg expression, but current therapies for HBV do not achieve this. Lamivudine, a nucleoside analog that potently inhibits HBV replication, has no efficacy on HDV viremia or liver disease activity in patients with chronic hepatitis D. 7,8 Likewise, other antiviral agents such as suramin, acyclovir, ribavirin, and famcyclovir, as well as immunomodulating agents such as steroids, thymosin, levamisole, and thymic humoral factor-gamma 2 have proved ineffective against HDV. 9 Clevudine, another nucleoside analog that potently suppresses HBV replication, 10 was recently shown to suppress HDV replication in the woodchuck model.…”
mentioning
confidence: 99%